Nutritional status and factors associated with undernutrition among tuberculosis patients in Sri Lanka - O. Rajapakshe; N. H. S. Nadeeka; P. Liyanage (College of Community Physicians of Sri Lanka, 2023)
Introduction: Apart from COVID-19, tuberculosis (TB) is the leading cause of death among infectious diseases globally and in Sri Lanka. It is known that the high-risk groups for developing TB are from lower socio-economic groups. Further, there is a close link between TB and nutrition. Objectives: To assess the prevalence and associated factors of undernutrition among TB patients in Sri Lanka Methods: A cross-sectional study was carried out using secondary data of a 2020 cohort of TB patients. Results: Out of 4566, the majority were males (65.2%). According to age groups, 55-64-year age group reported the highest proportion of patients (n=1018; 22.3%). According to the classification of body mass index (BMI), 46.3% were underweight. In bivariate analysis, gender (p=0.07), presence of comorbidities (p<0.001), site of TB (p<0.001), use of alcohol (p=0.01), site of TB (p<0.001), treatment category (p<0.001), smoking (p<0.001), alcohol use (p=0.04) and illicit drug use (p<0.001) were associated with patients being underweight. In multivariate analysis, only presence of comorbidities (p<0.001), site of TB (p<0.001), treatment category (p<0.001), smoking (p=0.04) and illicit drug use (p=0.02) were associated with patients being underweight. Conclusions & Recommendations: Creating awareness among clinicians and public health staff is important for them to be vigilant about TB patients with above associated factors. Proper nutritional counselling must be carried out for TB patients. Further, in implementing available nutritional interventions and patient awareness programmes, patients with lower BMI should be given priority although all TB patients are considered in need of nutritious diet.